PENGARUH SUMBER DAYA MANUSIA DAN LINGKUNGAN WIRAUSAHA TERHADAP UPAYA MENGURANGI PENGANGGURAN DI KABUPATEN GOWA - Andi Widiawati (Jurnal Bisnis dan Kewirausahaan, 2019)
MSMEs in Gowa Regency have increased compared to the previous year. Nevertheless, the increase in the number is not necessarily followed by business success. For this reason, it is important to know what factors influence MSME performance. This study aims to determine the effect of factors on MSME performance. The type of research used is descriptive. The analytical method used is qualitative descriptive analysis, namely secondary data analysis, namely data obtained from scientific journals, documents, books, articles and the Internet. The results of the discussion showed the characteristics of human resources, environmental characteristics, entrepreneurial characteristics and unemployment have a relationship level and have a positive effect on the performance of MSMEs. It is recommended that MSMEs always improve quality, pay attention to the environment to add experience, be consistent in running a business, improve equipment and the willingness to use new technology